Mastering social foresight – introduction to the special issue. Issue 2 (11th May 2015) - Poli, Roberto
Abstract : Purpose: – The purpose of this paper is a presentation of the guiding ideas underlining the master degree course in social foresight recently launched by the University of Trento (Italy). Design/methodology/approach: – This paper is a reconstruction of the guiding ideas that have been used for designing the social foresight master degree. Findings: – Students are exposed to a mix of contributions from futures studies, the human and social sciences (including psychology of decisions, social change, values and secondary analysis techniques) and mathematics (not only statistics, but also system theory and simulation). Originality/value: – A unique look at the ideas behind the master degree course in social foresight at the University of Trento (Italy).